2018
DOI: 10.1111/pbi.13033
|View full text |Cite
|
Sign up to set email alerts
|

Morphological dissection and cellular and transcriptome characterizations of bamboo pith cavity formation reveal a pivotal role of genes related to programmed cell death

Abstract: Summary Pith cavity formation is critical for bamboo to overcome the bending force during its fast growth; however, the underlying molecular mechanisms remain largely unknown. Multiple approaches, including anatomical dissection, mathematical modelling and transcriptome profiling, were employed in this study to investigate the biology of pith cavity formation in bamboo Pseudosasa japonica . We found that the corruption of pith tissue occurred sequentially and asymmetrically fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Rapid growth of moso bamboo was observed shortly after the young shoots emerged from the ground [ 43 ]. GA is a critical phytohormone involved in rapid growth, and the spatial and temporal distribution of GA is strictly regulated [ 44 , 61 ]. The top portion of young bamboo shoots contain GA at a concentration higher than that in the basal portion [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid growth of moso bamboo was observed shortly after the young shoots emerged from the ground [ 43 ]. GA is a critical phytohormone involved in rapid growth, and the spatial and temporal distribution of GA is strictly regulated [ 44 , 61 ]. The top portion of young bamboo shoots contain GA at a concentration higher than that in the basal portion [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid growth of moso bamboo occurs after the young bamboo shoots are covered with a shell and emerge from the ground. PCD was revealed to occur in pith cavity formation during rapid bamboo growth [ 44 ]. During the bamboo rapid-growth stage, cell division gradually decreases, while cell elongation and secondary cell wall thickening also occur [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the shoot apical meristem (SAM) plays an important role in the development of bamboo culm wall thickening. A larger SAM leads to elevated levels of hormones (e.g., cytokinin and growth hormone) and upregulation of hormone signaling and downstream functional genes (e.g., metabolism-related genes), ultimately leading to thickening of the bamboo culm wall [41]. The growth of SAM requires large amounts of energy and nutrients, which is consistent with the results of this study showing that many differential genes are enriched in the metabolic pathway of starch and sucrose and oxidative phosphorylation.…”
Section: Reticulation Pathway For Bamboo Culm Wall Thickness Controlmentioning
confidence: 99%
“…where n is a real number. This equation has been shown to be valid for describing the actual cross-sections of tree rings and bamboo shoots [2][3][4][5]. Equation (3) in polar coordinates can be rewritten as…”
Section: Introductionmentioning
confidence: 99%
“…where n 1 , n 2 and n 3 are constants (both ∈ R); positive integer m was introduced to make the curve generate arbitrary polygons (with m angles) consequently enhancing the flexibility of Lamé curves. We refer to Equation (5) as the original Gielis equation (OGE) in the following text for simplicity. OGE has been used to simulate many natural shapes, e.g., diatoms, eggs, cross sections of plants, snowflakes and starfish [1,2].…”
Section: Introductionmentioning
confidence: 99%